Single-photon source based on FWM with adjustable linear SOP - Almeida, Álvaro J. (2012)
We present a setup able to generate and detect single photons in optical fibers using the stimulated four-wave mixing (FWM) process. The results show an accurate generation of single photons at four different linear states of polarization (SOPs), with angles 0, 45, 90 and -45 degrees. The detection was performed in back-to-back configuration and after transmission over an optical fiber with a length up to 10 m.